IMPROVING ELDERLY DIGITAL HEALTH LITERACY THROUGH MOBILE JKN ASSISTANCE AT HELVETIA PRIMARY HEALTH CENTER MEDAN - Apriliani Apriliani; Widiya Nisa; Dewi D.S Butar Butar; Willyansyach Willyansyach (Journal of Gender and Social Inclusion in Muslim Societies, 2026)
The utilization of BPJS Kesehatan thru the Mobile JKN application is one of the efforts to support the transformation of digital health services and improve the efficiency of family health financing. However, the utilization of the application among the elderly group is still low due to limited knowledge and skills in using digital services. This community service activity aims to enhance the knowledge and skills of the elderly in utilizing the Mobile JKN application at UPT community health center Helvetia Medan. The activity was carried out using an educative-participative approach thru community education methods, technology diffusion, training, mentoring, mediation, and advocacy. The target of the activity is 30 elderly participants of BPJS Kesehatan. Evaluation was conducted using a one group pre-test and post-test design, while participants' skills were assessed thru observation sheets during the practice of using the Mobile JKN application. The results of the community service activities showed that the average knowledge score increased from 3.43 ± 1.251 before education to 7.47 ± 1.697 after education, with statistical tests indicating a significant difference (p < 0.001). In addition, the majority of participants were able to use the basic features of the Mobile JKN application, such as downloading the application (96.7%), registering an account (90.0%), logging into the application (90.0%), and checking membership status (86.7%). This activity shows that education accompanied by practice and mentoring effectively improves the digital health literacy of the elderly in utilizing BPJS Kesehatan thru the Mobile JKN application. Similar programs need to be implemented continuously as part of the strategy to enhance access to digital health services for the elderly group Keywords : BPJS Kesehatan, Mobile JKN, Elderly, Community Empowerment